2019
DOI: 10.3390/atmos10100608
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Probabilistic Forecasts of Heavy Rainfall in Mountainous Areas of the Wujiang River Basin in China Based on TIGGE Data

Abstract: Based on the ensemble precipitation forecast data in the summers of 2014–2018 from the Observing System Research and Predictability Experiment (THORPEX) Interactive Grand Global Ensemble (TIGGE), a comparative study of two multi-model ensemble methods, the Bayesian model average (BMA) and the logistic regression (LR), was conducted. Meanwhile, forecasts of heavy precipitation from the two models over the Wujiang River Basin in China for the summer of 2018 were compared to verify their performances. The trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…It combines the forecast distributions of different models and builds a weighted predictive distribution from them. Many empirical studies including those in [8,9,22,[41][42][43] have shown that various BMA approaches outperform other competitors, including a single best model and a simple averaging in prediction performance.…”
Section: Bayesian Model Averagingmentioning
confidence: 99%
“…It combines the forecast distributions of different models and builds a weighted predictive distribution from them. Many empirical studies including those in [8,9,22,[41][42][43] have shown that various BMA approaches outperform other competitors, including a single best model and a simple averaging in prediction performance.…”
Section: Bayesian Model Averagingmentioning
confidence: 99%
“…Although there are lots of studies concentrating on precipitation forecasts [26,27] and streamflow predictions [10,28] for TIGGE and the effectiveness of postprocessing methods [5,29,30], few studies explore both the performances of TIGGE ensemble precipitation forecasts and their applicability in streamflow predictions over mountain river basins. Qi, Zhi [27] investigated the performances of the raw and postprocessed ensemble forecasts of heavy precipitation in mountainous areas, while they did not investigate their performances in ensemble streamflow prediction. This study aims to evaluate raw and postprocessed EPFs and assess the degree of improvement with different postprocessing methods to verify the reliabilities of EPF and ESP in a western mountain basin of China.…”
Section: Introductionmentioning
confidence: 99%